Nursing care in the mental health of school adolescents residing in a vulnerable area of North Lima - Asencios-Trujillo, Lucia; Asencios-Trujillo, Lida; La Rosa-Longobardi, Carlos; Gallegos-Espinoza, Djamila; Piñas-Rivera, Livia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Mental healthduring the COVID-19 pandemic has been one of the greatest negative impacts that the population has had worldwide, which makes them more susceptible to mental disorders as a result, so the research objective is to determine the mental health of School Adolescents residing in a vulnerable area of North Lima. It is a quantitative, descriptive-transversal study, with a population of 306 participants who answered a questionnaire of sociodemographic aspects and the scale of depression, anxiety and stress. In the results we observed that 30,7 % presented extremely severe depression, 8,8 % severe depression, 19,3 % moderate depression, 12,4 % mild depression and 28,8 % normal depression. In conclusion, measures should be taken to provide mental health care to vulnerable School Adolescents.